ChemInform Abstract: Mild Regiospecific Synthesis of 1‐Alkoxy‐isochromenes Catalyzed by Well‐Defined [Silver(I)(Pyridine‐Containing Ligand)] Complexes. Issue 42 (14th October 2014) - Dell'Acqua, Monica; Castano, Brunilde; Cecchini, Clara; Pedrazzini, Tommaso; Pirovano, Valentina; Rossi, Elisabetta; Caselli, Alessandro; Abbiati, Giorgio
Abstract The new silver catalysts (AGC) and (ATF) efficiently promote the ring closure reaction of 2‐alkynylbenzaldehydes with primary and secondary alcohols.